The absolutist - Boyne, John, 1971- (Other Press, 2012)
It is September 1919: twenty-one-year-old Tristan Sadler takes a train from London to Norwich to deliver a package of letters to the sister of Will Bancroft, the man he fought alongside during the Great War. But the letters are not the real reason for Tristan's visit. He can no longer keep a secret and has finally found the courage to unburden himself of it. As Tristan recounts the horrific details of what to him became a senseless war, he also speaks of his friendship with Will--from their first meeting on the training grounds at Aldershot to their farewell in the trenches of northern France. The intensity of their bond brought Tristan happiness and self-discovery as well as confusion and unbearable pain. The Absolutist is a masterful tale of passion, jealousy, heroism, and betrayal set in one of the most gruesome trenches of France during World War I. This novel will keep readers on the edge of their seats until its most extraordinary and unexpected conclusion, and will stay with them long after they've turned the last page.